Exploring the relationship between mental work load, work ability, and musculoskeletal disorders: A cross-sectional modeling study among health service workforces in Iran - Maryam Rafiee; Ali Alboghobeish; Mahnaz Saremi; Sayed Vahid Esmaeili (PLoS ONE, 2025)
Introduction The health service workforces play a crucial role in shaping a nation’s health system efficiency, making it vital to understand factors affecting their performance. This study examined the relationship between mental workload, work ability, and work-related musculoskeletal disorders (WMSDs) among employees at comprehensive health service centers in Saveh, Arak province, Iran. Materials & Methods The cross-sectional study involved 197 randomly selected personnel whose WMSDs prevalence was evaluated using the Nordic questionnaire. Work ability was assessed through the Work Ability Index (WAI), and mental workload was measured using the NASA Task Load Index (NASA-TLX). All data analysis was performed using SPSS v 24.0 software. Results The average age and work experience of the participants were determined to be 35.74 ± 7.52 and 11.63 ± 8.59 years, respectively. The highest prevalence was reported in the lumbar region, with a lifetime prevalence of 63.5% and an annual prevalence of 60.9%. The average mental workload and work ability were calculated to be 63.24 ± 13.26 and 34.86 ± 7.61, respectively. The highest prevalence of WMSDs (89.5%) was observed in the lower back region among women aged 45–54 years. A significant relationship was identified between work experience and age with work ability and mental workload (P < 0/01). Furthermore, an increase of one point in work ability score leads to a decrease in WMSDs in the neck, wrists/hands, low back and hips/thighs regions by 13.5%, 8%, 11.5%, and 9%, respectively. Conclusions The study underscores the need to enhance the physical, psychological, and social environments of health service employees. Implementing targeted educational programs can improve task performance and mitigate high mental workload effects, ultimately reducing WMSDs and improving staff well-being.